Social Support and Loneliness Among Chinese Caregivers of Children With Chronic Kidney Disease During the COVID-19 Pandemic: A Propensity Score Matching Analysis - Shi, Lin; Zhang, Hengci; Yang, Haiping; Wu, Daoqi; Li, Xiaoqin; Zhang, Yunzhi; Chen, Xuelan; Wang, Mo (Frontiers in Pediatrics, 2021)
To evaluate social support and loneliness as well as their association among caregivers of children with chronic kidney disease (CKD) from China during the coronavirus disease 2019 (COVID-19) pandemic. We collected data for caregivers of children with CKD and caregivers of healthy children and matched the two groups using propensity score matching (PSM). We compared the differences in social support and loneliness between the two groups after matching and analyzed the relationship between social support and loneliness in the observation group. Before PSM, we analyzed the data for 247 caregivers of children with CKD and 315 caregivers of healthy children from 13 provinces. After PSM, the two groups each included 202 caregivers. The social support score of caregivers of children with CKD was lower than that of caregivers of healthy children (P<0.002), while the loneliness score was higher for caregivers of children with CKD than for caregivers of healthy children (P<0.008). The social support score was negatively correlated with the loneliness score [r = -0.598, P<0.001]. Caregivers of children with CKD experienced less social support and greater loneliness than caregivers of healthy children during the COVID-19 pandemic. Therefore, greater attention should be paid to providing social support for caregivers of CKD children and to improving the ability of these caregivers to cope with loneliness.